ハンドヘルドダイナモメーターを用いた新しい膝伸展筋力測定方法の臨床的有用性 - 徳久 謙太郎; 鶴田 佳世; 宇都 いづみ; 梛野 浩司; 岡田 洋平; 生野 公貴; 高取 克彦; 松尾 篤; 冷水 誠; 庄本 康治 (理学療法学, 2007)
We developed a new measurement method for the isometric knee extensor strength with a hand-held dynamometer (HHD). The purpose of this study was to assess the clinical utility of the new method by examining the interrater reliability between male and female rater, validity and simplicity. The subjects were 31 community-dwelling elderly people (9 male, 22 female, mean age 81.6±6.1 years) who were receiving a day-care rehabilitation program. Their isometric knee extensor strength were measured three times by this method and the belt method that fixed a HHD by a belt. The time to finish the measurement was recorded under the condition that the rater was masked. As a result, intraclass correlation coefficient (ICC), which represents interrater reliability between male and female rater, was 0.96. There were no significant differences in the measurement values between this method (male and female rater) and the belt method. ICCs of the belt method were 0.89 in male rater and 0.90 in female rater. The time to finish the measurement by this method was 2 minutes and 12 seconds (± 40 second) on average, which was significantly shorter than the belt method (p<0.05). From these results, the reliability, validity and simplicity for the frail elderly of this new method were considered acceptable. 我々はハンドヘルドダイナモメーター（HHD）を使用した，徒手による等尺性膝伸展筋力測定の際に問題となる「検者のHHD固定能力不足」を改善した新しい測定方法を考案した。本研究の目的は，虚弱高齢者を対象に，この新測定法の男女検者間再現性，妥当性，簡便性を明らかにし，本法の臨床的有用性を検討することである。対象は当院通所リハビリテーションを利用している虚弱高齢者31名（男性9名，女性22名，平均年齢81.6±6.1歳）である。各対象者に対して等尺性膝伸展筋力測定を，本法にて男女検者が1回ずつ，ベルトでHHDを固定する方法（ベルト法）にて1回，合計3回実施した。また本法とベルト法による筋力測定所要時間を検者にマスクした状態で測定した。結果として，男・女性検者による本法での測定値間の級内相関係数は0.96であり，男女検者間再現性は良好であった。本法（男・女検者）とベルト法での測定値の3群間に統計学的有意差は認められず，ベルト法と本法での測定値間の級内相関係数は，男性検者で0.89，女性検者で0.90であり，併存的妥当性は良好であった。本法による1回の筋力測定所要時間は，ベルト法より有意に短く（p<0.05），平均2分12秒であった。この新測定法は虚弱高齢者の等尺性膝伸展筋力測定を行うにあたり，臨床的に有用な測定方法であることが示唆された。